Industrial training report: Keretapi Tanah Melayu Berhad (KTMB) / Nurul Hani Hasbolah - Hasbolah, Nurul Hani (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report is an overview of the industrial training experience I have underwent for 8 weeks in Keretapi Tanah Melayu Berhad (KTMB) Headquarters, as an Information Management Diploma Student. I was placed in the Information and Communication Technology (ICT) Department, specifically in the Administration Governance and Compliance (AGC) Unit under the supervision of Mrs. Nurul Hidayah binti Hasan. This program aims to provide the students the chance of applying the knowledge from their students into professional settings. During this period, I was assigned with tasks that focus on document management and was exposed to the organization’s technological infrastructure and support systems. Furthermore, I have also developed vital skills and encountered to challenges and complexity through hands-on experience as well as my involvement in ICT Department’s daily operations. Through this training, I have accomplished several significant projects by applying theoretical knowledge practically. This report also outlines a range of suggestions to both IMD310 and KTMB for future initiatives to improve this program. In conclusion, this industrial training was crucial in encouraging both professional and personal growth by providing valuable insights om how ICT is used in a large organization.